2019
DOI: 10.1080/10494820.2019.1620290
|View full text |Cite
|
Sign up to set email alerts
|

Interaction patterns in exploratory learning environments for mathematics: a sequential analysis of feedback and external representations in Chinese schools

Abstract: Feedback in intelligent tutoring systems has been depicted as an important contributor to encourage exploration. However, few studies have explored learners' interaction patterns associated with feedback and the use of external representations in exploratory learning environments. This study used Fractions Lab, an exploratory learning environment for mathematics, to facilitate children's conceptual understanding of fractions in three Chinese schools. Students (n = 189) from six different classes were invited t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…However, revealing all the behaviors and analyzing them in detail is essential in designing the teaching environment and choosing the appropriate pedagogical approaches. In this research, a comprehensive investigation of event chains was made by conducting an in-depth examination of behavior patterns with lag sequential analysis (Zhang et al, 2019). In addition, preservice teachers’ driver–navigator behaviors were discussed for the first time (Cetin, 2016; Mentz et al, 2008; Vasconcelos & Kim, 2020; Zha et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, revealing all the behaviors and analyzing them in detail is essential in designing the teaching environment and choosing the appropriate pedagogical approaches. In this research, a comprehensive investigation of event chains was made by conducting an in-depth examination of behavior patterns with lag sequential analysis (Zhang et al, 2019). In addition, preservice teachers’ driver–navigator behaviors were discussed for the first time (Cetin, 2016; Mentz et al, 2008; Vasconcelos & Kim, 2020; Zha et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…They found that global students demonstrated iterative behaviour, while sequential students showed sequential behaviour. Similarly, LSA was applied by Zhang et al (2021) to demonstrate how students interact with three‐level feedback and the various external representations in an exploratory mathematical learning environment. Recently, Tlili et al (2021) applied LSA to investigate how cultural diversity affects students' learning behavioural patterns in open and online courses.…”
Section: Literature Reviewmentioning
confidence: 99%
“…One approach is lag sequential analysis (LSA), which highlights significant sequential behaviours in relation to the temporal dimension Knight et al, 2017). LSA is commonly used for analyzing the learning trajectories of those participating in learning activities in guided or well-designed explorative and collaborative environments (e.g., Li et al, 2021;Sun et al, 2021;Zhang, Gao et al, 2019;Zheng et al, 2021). The identified patterns of sequential behaviours could help researchers and instructors provide personalized feedback (Hou, 2012;Hwang & Chen, 2017;Yin et al, 2017), promote knowledge construction (Lan et al, 2012;Lin et al, 2013;Yang et al, 2015), etc.…”
Section: Using Network Analytics To Understand Online Learning Behavi...mentioning
confidence: 99%